THE RELATIONSHIP BETWEEN SOCIO-ECONOMIC AND MEDIA LITERACY LEVELS WITH THE LEVEL OF PARENT PARTICIPATION IN PREVENTING STUNTING IN RURAL AREAS - Chawa, Anif Fatma; Fitriana, Titi; Ambarsari, Zulia Antan (Universitas Padjadjaran, 2024)
This article examines the relationship between two variables: socioeconomic level and media literacy (variable X) and parental participation in stunting prevention (variable Y) in Indonesia. Socioeconomic level has long been considered the most dominant factor influencing the risk of stunting in children. This study introduces an additional variable, media literacy, hypothesizing that it may also impact parental participation in preventing stunting in children. The study employs a quantitative explanatory method using Kendall's rank correlation test. The population consists of parents with children under five years old. Sampling was conducted in two stages. First, the sample size was calculated based on the total population across eight Pre- and Postnatal Healthcare Information Centres (Posyandu) with a 5% margin of error. Second, the sample size obtained was distributed proportionally among each Posyandu using simple random sampling. The results show no significant relationship between socioeconomic level and parental participation in stunting prevention, with a significance level of 0.25. However, a relationship was found between media literacy and parental participation in stunting prevention, with a significance level of 0.023 and a very weak correlation coefficient of 0.109 (or 11%). This suggests that higher media literacy among parents has the potential to increase their participation in stunting prevention, albeit the relationship is very weak. This may be because parents do not directly use social media to obtain stunting information but rather for other purposes, such as entertainment or accessing nutritious recipes for children. Additionally, parents may receive stunting information from other sources, including stunting education provided by Posyandu cadres, village midwives, doctors, and nutrition consultants from local health centres.